Survivals of mouse oocytes approach 100% after vitrification in 3-fold diluted media and ultra-rapid warming by an IR laser pulse() - Jin, Bo (2014)
Vitrification is the most sought after route to the cryopreservation of animal embryos and oocytes and other cells of medical, genetic, and agricultural importance. Current thinking is that successful vitrification requires that cells be suspended in and permeated by high concentrations of protective solutes and that they be cooled at very high rates to below − 100°C. We report here that neither of these beliefs holds for mouse oocytes. Rather, we find that if mouse oocytes are suspended in media that produce considerable osmotic dehydration before vitrification and are subsequently warmed at ultra high rates (10,000,000°C/min) achieved by a laser pulse, nearly 100% will survive even when cooled rather slowly and when the concentration of solutes in the medium is only 1/3(rd) of standard.